Heterogeneous Associative Plasticity in the Auditory Cortex Induced by Fear Learning – Novel Insight Into the Classical Conditioning Paradigm. - ZELENKA, Ondrej; NOVAK, Ondrej; BRUNOVA, Aneta; SYKA, Josef (Physiological Research, 2021)
We used two-photon calcium imaging with single-cell and celltype resolution. Fear conditioning induced heterogeneous tuning shifts at single-cell level in the auditory cortex, with shifts both to CS+ frequency and to the control CS- stimulus frequency. We thus extend the view of simple expansion of CS+ tuned regions. Instead of conventional freezing reactions only, we observe selective orienting responses towards the conditioned stimuli. The orienting responses were often followed by escape behavior.